Capacitive electrode with high sensitivity for detection of electrical biopotentials - Varela Benítez, J. L.; Rivera-Delgado, J. O.; Espina-Hernández, J. H.; de la Rosa-Vázquez, J. M. (Revista Mexicana de Ingenieria Biomedica, 2015)
In this work, the design and implementation of a capacitive non-contact electrode for detecting biopotentials in the human body is presented. Electrical circuits, the selection criteria of the operational amplifier based on the analysis of the optimal noise resistance are presented, the physical assembly is described and the signals obtained and evaluation of its performance are presented based on the signal-to-noise ratio S/N. We show the performance of several operational amplifiers and it is shown the versatility of the electrode to detect several biopotentials making adjustments to the values of two electrical components of the electrode.